A Timely Shift from Shotgun to Targeted Proteomics and How It Can Be Groundbreaking for Cancer Research - Faria, Sara S.; Morris, Carlos F. M.; Silva, Adriano R.; Fonseca, Micaella P.; Forget, Patrice; Castro, Mariana S.; Fontes, Wagner (Frontiers in Oncology, 2017)
The fact that cancer is a leading cause of death all around the world has naturally sparked major efforts in the pursuit of novel and more efficient biomarkers that could better serve as diagnostic tools, prognostic predictors or therapeutical targets in the battle against this type of disease. MS based proteomics has proven itself as a robust and logical alternative to the immuno-based methods that once dominated the field. Nevertheless, intrinsic limitations of classic proteomic approaches such as the natural gap between shotgun discovery-based methods and clinically applicable results have called for the implementation of more direct, hypothesis-based studies such those made available through targeted approaches, that might be able to streamline biomarker discovery and validation as a means to increase survivability of affected patients. In fact, the paradigm shifting potential of modern targeted proteomics applied to cancer research can be demonstrated by the awesome number of advancements and increasing examples of new and more useful biomarkers found during the course of this review in different aspects of cancer research. Out of the many studies dedicated to cancer biomarker discovery, we were able to devise some clear trends, such as the fact that breast cancer is the most common type of tumor studied and that most of the research for any given type of cancer is focused on the discovery of diagnostic biomarkers, with the exception of those that rely on tumor tissue samples, which are generally aimed towards prognostic markers. Interestingly, the most common type of targeted approach is based on SID-SRM protocols for quantification of the target molecules. Overall, this reinforces the notion that targeted proteomics has already started to fulfil its role as a groundbreaking strategy that may enable researchers to catapult the number of viable, effective and validated biomarkers in cancer clinical practice.